Structural behaviour of stud shear connections in composite floors with various connector arrangements and profiled deck configurations. (1st May 2020) - Shen, Min-hui; Chung, Kwok-Fai; Elghazouli, Ahmed Y.; Tong, Jing-Zhong
Highlights: Establish finite element models on stud shear connections in composite beams. Provide various load transfer mechanisms within the connections. Present detailed stress distributions around shear studs and within "trough" concrete. Understand various failure modes through the "stress and strain" conditions. Tabulate shear resistances for various connection arrangements and configurations. Propose a configuration parameter for accurate prediction on the shear resistances. Abstract: This paper investigates the structural behaviour of stud shear connections in composite floors with various connector arrangements and profiled deck configurations. The numerical investigation adopts a number of advanced finite element models which have been carefully calibrated against standard push-out tests conducted by the authors. In order to capture the complex interactions that take place between the concrete and the headed shear studs, a number of distinctive load transfer mechanisms within the solid concrete and the profiled composite slabs are identified and discussed. Detailed parametric studies are then undertaken using the calibrated models for the purpose of quantifying the shear resistance and deformation characteristics for connections with various stud and deck arrangements. A configuration parameter β is proposed for use in conjunction with the reduction factor kt given in EN 1994-1-1 to incorporate the effects of installation positions of headed shear studs and trough widths of profiled decks as well as the presence of longitudinal stiffeners if any. It is shown that the values of β are in the range of 0.55 to 1.0, which are significantly smaller than those commonly allowed for in the design of stud shear connections in composite floors.